A way to support the transformation methods for the data in a semantic network - E. Wolfengagen, Viacheslav; Yu. Ismailova, Larisa; V. Kosikov, Sergey (International Journal of Engineering and Technology, 2018)
The paper considers the problem of building of the transformable object-relation mapping. It is shown that an essential part of the task is to get the conversion of data objects doing their representation adjusted for the corresponding data model. It is offered to receive the de- cision by a semantic method in case of which the formal models of object system and relational system are considered and their interpre- tations are set. The transformation mappings are considered as a kind of mappings saving interpretations of the given form. Creation of model of converting of data objects on the basis of applicative computing systems is offered what allows to build models of both object, and relational systems dipping in applicative structures with the given means of expression, in particular, to use a lambda-algebra or a lambda model. On this basis the models can be received allow compositions of means of converting and also determination and check of global restrictions for the changes of data determined by the given set of methods of converting. Achievement of flexibility requires use parameterization of the considered construction, i.e. support of dependence of a set of available methods of interpretation on parameters as which semantic characteristics of processed data appear. The prototypes of constructions of models have been used for informational legal supporting of implementation of the best available technology (or just BAT) in practice in Russia.Â Â